Suicidality in detention centres: a case study. Issue 1 (6th March 2017) - Rimkeviciene, Jurgita; O'Gorman, John; De Leo, Diego
Abstract : Purpose: Recent reports raise suicidality among asylum seekers as a pertinent issue in current Australian offshore detention centres. However, knowledge on the nature of the suicidality in these centres is very limited. The purpose of this paper is to explore in depth how suicidality arises and develops in offshore detention centres. Design/methodology/approach: A single case study approach was used. Findings: This case study presents the findings on the suicidal process of an asylum seeker who attempted suicide three times while in Nauru Regional Processing Centre, the last of which being a near-lethal one. The prolonged mandatory detention, together with lack of clarity about the timeframes of detention and constant postponing of the legal processes were identified as the main factors driving the suicidal intent. The suicidal behaviour escalated from an interrupted attempt to a near lethal one within two years, which signals lack of adequate suicide prevention within detention. Practical implications: The resources for mental health being limited in Nauru, it is likely overall changes in refugee status processing may be a more effective suicide prevention strategy rather than implementation of other additional measures. Originality/value: Studies in offshore processing facilities have been scarce due to barriers for researchers to access the detention centres. This study offers a unique insight into suicidality in this hard to reach population.